Semantic and cognitive barriers to the noosymbiosis of humanity and biosphere - Korsak, Kostiantyn; Korsak, Yurii (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2021)
The article proves that the model of evolution in the form of "three waves” (Alvin Toffler, USA) must be supplemented with the 4th noowave. Its basis is the ecologically perfect technologies (nootechnologies) noticed by the authors, capable of eliminating the threats of pandemics and ecological collapse. In 2000, there were two of them, in 2010 – 4, in 2019 – 8. Within two years, their number increased to almost 30, which is evidenced by the arrival of the 4th noowave. The scientific world does not believe in the reality of ecologically perfect productions and rejects the author’s proposals. Western journals rejected all our articles, in the Russian Federation and Ukraine they were published, but did not receive full recognition. This can be explained by the fact that in the West, after the discussions in 1955-1970, the definition of the noosphere as an immaterial (spiritual) shell of the Earth dominates (Pierre Teilhard de Chardin, France). This excludes the perception of nootechnology as material entities, which denies progress and the elimination of global threats. The authors have created a dictionary (Nooglossary-2) containing the term "noosphere” and nooconcepts "from the future” (these are nootechnologies, nooprocesses and noosciences). It is necessary to accelerate the construction of the noosphere in its material embodiment (according to Volodymyr Vernadsky).